Analysis of Behaviorism Theory in Arabic Language Learning: Relevance and Criticism- A Literature Review - Kharirotun Nafisah; Yolda Mutiara; Ahmad Nur Mizan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze behaviorism theory in Arabic language learning by focusing on the aspects of relevance and criticism regarding its implementation. The method used is qualitative research with a literature review approach, conducted through the collection and analysis of various literature sources related to behaviorism theory and Arabic language learning. The data were analyzed descriptively and analytically to identify the main concepts, forms of implementation, as well as the strengths and limitations of behaviorism theory. The results of the study show that behaviorism theory still has relevance in Arabic language learning, especially at the initial stage of learning. This approach is effective in forming language habits through repetitive exercises, imitation, and reinforcement, thereby helping students master basic aspects such as pronunciation, vocabulary, and simple sentence patterns. However, this theory also has weaknesses, as it tends to be mechanical, pays less attention to cognitive processes, and has not been able to optimally develop communication skills.Based on these findings, it can be concluded that behaviorism theory can still be applied in Arabic language learning, but it needs to be combined with other approaches that are more communicative and contextual. This is intended so that the learning process not only focuses on habit formation but is also able to develop comprehensive language skills.